Nasopharyngeal Dimensions in Relation to Some Dento-Cranial Variables in Class I and II Skeletal Patterns (A Comparative Cephalometric Study) - Fadel, Ammar A; Ali, Fakhri A (Journal of Baghdad College of Dentistry, 2015)
Background: The size of the nasopharyngeal airway was believed to have an important role in the development of the dentofacial structure. This study was carried out to test the relation between the nasopharyngeal dimensions with some dento-cranial measurements in class I and II jaw relationship. Materials and Methods: This study was done on 60 subjects (30 males and 30 females) at age range 18-25 years. Cephalometric radiograph has been taken to each subject and the measurements were recorded. The sample was divided into two groups, class I skeletal relationship (15 males and 15 females) and class II skeletal relationship (15 males and 15 females). Comparisons between the different study groups were undertaken.Results: In class I skeletal relationship, all the nasopharyngeal liner measurements and all the dento-cranium linear measurements are significantly higher in males than females, except lower airway thickness (PNS-ad1) and upper airway thickness (PNS-ad2) showed no significant gender difference. While all the angular measurements showed no significant gender difference. In class II skeletal relationship, most of the nasopharyngeal liner measurements have no significant gender difference, while all the dento-cranium linear measurements are significantly higher in males than females.Conclusion: In comparison for class difference between class I and class II skeletal relations in total sample, all the nasopharyngeal linear measurements have no significant class difference, except lower airway thickness showed significant difference which was higher in class II than class I and upper airway thickness showed significant difference which was higher in class I than class II. In the whole sample of the study, positive correlation was found between lower airway thickness and upper airway thickness.